Penerapan Spiritual Coping pada Mahasiswa yang Mengalami Kecemasan dalam Menyelesaikan Tugas Akhir - Lisa Devita Sarippi; Muslimah Zahro Romas (Pusat riset dan Inovasi Nasional, 2026)
Anxiety in completing a final thesis is a common issue experienced by final-year students, which can affect academic performance, mental health, and even delay graduation. This condition highlights the importance of effective strategies to manage psychological pressure appropriately. This study aims to explore the application of spiritual coping in helping students reduce anxiety during the thesis writing process. The research employed a qualitative approach with a descriptive design. The participants consisted of three students selected from a total of thirteen who had been identified with severe anxiety. The instruments used were the Taylor Manifest Anxiety Scale as an initial assessment, followed by in-depth interviews and observations to explore their experiences, coping strategies, and psychological dynamics. Data were analyzed thematically by focusing on the personal, social, environmental, and religious domains in the practice of spiritual coping. The findings indicate that spiritual coping assists students in managing emotions, discovering life meaning, and maintaining academic commitment. Religious practices, prayer, spiritual reflection, and social support proved effective in fostering inner peace and alleviating anxiety symptoms. In conclusion, spiritual coping can serve as an effective strategy to support students in facing academic pressures and in enhancing psychological well-being.